Impact of in-person versus online supervised multicentre multicomponent prenatal exercise programme on maternal physical activity, fitness and healthy lifestyle: the Active Pregnancy trial SPIRIT 2025-based protocol - Cristina Nogueira-Silva; Anna Szumilewicz; Rita Santos-Rocha; Marco Branco; Joana Prior de Freitas; Bárbara Castro; Adelaide Teixeira Pinto; Sandra Silva - Santos; Miguel Angel Oviedo-Caro; Anna Szablewska (BMJ Open Sport & Exercise Medicine)
Many studies have supported the positive effects of an active lifestyle on the prevention and treatment of pregnancy-related complications, as well as maintaining fitness and functionality. The COVID-19 pandemic has underscored the need for virtual approaches to health interventions; however, few studies have examined the effectiveness of these interventions. The Standard Protocol Items: Recommendations for Interventional Trials 2025 guidelines were followed to describe the protocol of the ACTIVE PREGNANCY trial, an intervention study that delivers a physical exercise programme in-person (IN) and online (ON) to improve maternal physical activity (PA), fitness and healthy lifestyle parameters in pregnant women. Pregnant women will be invited to participate in a multisite, multicomponent exercise programme delivered either IN or ON by qualified exercise physiologists. Both groups will receive an exercise intervention delivered in different real-life environments. Participants will undergo basic fitness field tests and complete questionnaires assessing PA, fitness and lifestyle parameters before starting the exercise programme and after completing 12 weeks of the intervention. Researchers will test whether the intervention is beneficial in maintaining or improving maternal parameters after 12 weeks and will compare the effectiveness of different exercise modes. Subgroups of maternal age and weekly volume of PA will also be analysed.Primary outcomes: PA volume and health-related and functional fitness. Secondary outcomes: healthy lifestyle parameters. Additional outcomes: satisfaction with the exercise interventions and resources. This study was approved by the Ethics Committee of Santarém Polytechnic University and registered on ClinicalTrials.gov (NCT06954454). Findings will be disseminated via publications, conferences and training programmes.